Juridical Review of Mortgage Enforcement on Ships and Its Legal Effects - Abas, Usman; Kariadi, Kariadi; Marthin, Sahertian (Journal of Law Justice (JLJ), 2025)
This study aims to determine what is the legal basis of collateral in general and ship mortgages in particular and legal consequences in this case obstacles in the execution of ship mortgages as collateral for debt repayment due to default. The research method used is Empirical Juridical, which analyzes the procedure for installing a ship mortgage as an object of debt collateral from the aspects of civil law, trade law, Law No. 4 of 1996 concerning Mortgage Rights and especially the legal basis for ship mortgages based on Law No. 17 of 2008 concerning Shipping materially ship mortgages as property guarantees or immovable objects which are treaty legal relationships that have legal consequences in fulfilling the rights and obligations of the parties. In addition, what are the legal consequences in the event of default by the debtor to the creditor (Banking Institution). This research was conducted at the Sorong Class I Harbor Authority and took information from the head of the ship's legal status section as a resource person. This data is analyzed in the form of a qualitative description. Problems in executing a mortgage against debt collateral due to default are the creditor as the owner of the ship has difficulty when wanting to take over, because the ship is always moving and its existence often moves even outside the territory of Indonesia, the cost of taking over the ship to be executed is quite high and when executed the ship is being rented by another party.